Disruptive innovation, stranded assets and forecasting: the rise and rise of renewable energy - Green, Jemma; Newman, Peter (Earthscan Ltd., 2017)
Disruptive innovations are seen to have three core features: 1. They occupy a niche that expands into being a major disruption to a technological system; 2. They grow exponentially and are thus very surprising in their disruption and 3. They create stranded assets. This paper shows how renewable energy with battery storage has the three core features of a disruptive innovation, and predicts that the number of fossil fuel stranded assets are thus likely to increase with the rise of renewable energy generation. Forecasts for the share of renewable capacity in global energy demand will go beyond current estimates, due to the introduction of battery storage and decline in retail renewable electricity prices, and could account for 100% of global energy demand in a number of different scenarios by 2050. We find that renewables and storage can be characterised as disruptive innovations and have the potential to change energy systems dramatically between now and 2050.